Factors that contribute to customer loyalty towards Telekom Malaysia Kuantan / Nurul Huda Hj Ismail - Hj Ismail, Nurul Huda (Bachelor Of Business Administration (Hons) Marketing, 2013)
In this study, the problem is to examine the factors that contribute to customer loyalty towards Telekom Malaysia Kuantan. The factors which focuses trust, brand image, service quality and customer satisfaction. Based on the questionnaire that being distribute to the customer at Kuantan area, this study was done to identify the relationship between that four factors and customer loyalty. The findings shows that trust, service quality and customer satisfaction are significant to customer loyalty towards Telekom Malaysia Kuantan